2011
DOI: 10.3233/jad-2010-100939
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Center Randomized Proof-of-Concept Clinical Trial Applying [18F]FDG-PET for Evaluation of Metabolic Therapy with Rosiglitazone XR in Mild to Moderate Alzheimer's Disease

Abstract: Here we report the first multi-center clinical trial in Alzheimer's disease (AD) using fluorodeoxyglucose positron emission tomography ([18F]FDG-PET) measures of brain glucose metabolism as the primary outcome. We contrasted effects of 12 months treatment with the PPARγ agonist Rosiglitazone XR versus placebo in 80 mild to moderate AD patients. Secondary objectives included testing for reduction in the progression of brain atrophy and improvement in cognition. Active treatment was associated with a sustained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 42 publications
1
59
0
Order By: Relevance
“…Moreover, pioglitazone prevented the accumulation of amyloid-b by increasing cerebral blood flow in patients with diabetes and Alzheimer's disease, which resulted in a significant improvement in MMSE scores [27]. Effective prevention of dementia onset by improvement in insulin resistance has been reported in several studies [28,29]. These studies may support our finding that pioglitazone was associated with a reduced risk of abnormal cognition by 50 %.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, pioglitazone prevented the accumulation of amyloid-b by increasing cerebral blood flow in patients with diabetes and Alzheimer's disease, which resulted in a significant improvement in MMSE scores [27]. Effective prevention of dementia onset by improvement in insulin resistance has been reported in several studies [28,29]. These studies may support our finding that pioglitazone was associated with a reduced risk of abnormal cognition by 50 %.…”
Section: Discussionsupporting
confidence: 73%
“…Typically these were short trials of a few weeks or up to 3 mo active treatment duration with 18 F-FDG PET before and during treatment (20)(21)(22). Trials that were extended for at least 6 mo also showed evidence of disease progression by further reduction of glucose metabolism in association cortices (23)(24)(25)(26). However, these trials had not been designed to assess progression.…”
Section: Discussionmentioning
confidence: 99%
“…In a small number of AD non-diabetic patients, 18-month treatment with pioglitazone (45 mg/day) as add-on therapy to the AChE inhibitors produced no significant treatment effect on cognition (Geldmacher et al 2011). Regardless the APOE status, no evidence of statistically or clinically significant efficacy in cognition or global function was detected for 2 mg or 8 mg rosiglitazone-extended release formulation (PPAR γ agonist) as adjunctive therapy to ongoing AChEIs in the two clinical phase III studies on AD patients (Harrington et al 2010;Tzimopoulou et al 2010). …”
Section: Insulin-sensitizing and Other Anti-diabetic Drugsmentioning
confidence: 99%